PENYULUHAN BUDIDAYA TANAMAN SAYURAN BAGI TIM PKK DI DESA MAKETE KECAMATAN GALELA BARAT, KABUPATEN HALMAHERA UTARA - Patty, Zeth; Yeane Kastanja, Ariance (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Hein Namotemo, 2021)
This community empowerment activity that has been carried out in Makete Village, West Galela District aims to provide knowledge and skills for mothers about organic vegetable cultivation. The method used is counseling about vegetable crop cultivation, which is accompanied by the manufacture of vegetable demonstration plots. The participants of this activity were PKK women from Makete Village as many as 20 people, who had tried to grow vegetables traditionally. The results of the evaluation of community service activities show that the knowledge and skills of the PKK group of Makete Village women who cultivate vegetables have increased. In addition, there has also been a change in understanding in cultivation techniques as has been done so far